2013
DOI: 10.1128/jb.00292-13
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of  V, an Extracytoplasmic Function   Factor of Bacillus subtilis, Is Controlled by Regulated Proteolysis of the Anti-  Factor RsiV

Abstract: During growth in the environment, bacteria encounter stresses which can delay or inhibit their growth. To defend against these stresses, bacteria induce both resistance and repair mechanisms. Many bacteria regulate these resistance mechanisms using a group of alternative factors called extracytoplasmic function (ECF) factors. ECF factors represent the largest and most diverse family of factors. Here, we demonstrate that the activation of a member of the ECF30 subfamily of ECF factors, V in Bacillus subtilis, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 58 publications
3
83
0
Order By: Relevance
“…A rasP::tet mutant showed a basal level σ V activity in the absence of HEWL ( Figure 1(c)). Whereas the addition of 100 ng/mL HEWL activated σ V several-fold in rasP + cells, the σ V activity level in the rasP::tet mutant did not change in the presence of 100 ng/mL HEWL (Figure 1(c)), indicating that the activation of σ V by HEWL requires RasP [5]. On the other hand, the approximately two-fold activation of σ V in the ∆ugtP mutant did not change when, in addition, rasP was disrupted (Figure 1(c)), indicating that RasP has nothing to do with the σ V activation by the lack of glucolipids.…”
Section: A Rasp Mutation Abolished the σ V Activation Caused By The Amentioning
confidence: 97%
See 3 more Smart Citations
“…A rasP::tet mutant showed a basal level σ V activity in the absence of HEWL ( Figure 1(c)). Whereas the addition of 100 ng/mL HEWL activated σ V several-fold in rasP + cells, the σ V activity level in the rasP::tet mutant did not change in the presence of 100 ng/mL HEWL (Figure 1(c)), indicating that the activation of σ V by HEWL requires RasP [5]. On the other hand, the approximately two-fold activation of σ V in the ∆ugtP mutant did not change when, in addition, rasP was disrupted (Figure 1(c)), indicating that RasP has nothing to do with the σ V activation by the lack of glucolipids.…”
Section: A Rasp Mutation Abolished the σ V Activation Caused By The Amentioning
confidence: 97%
“…The zinc chelator 1,10-phenanthroline (PT) inhibits the site-2 protease RasP [5], as it does many other site-2 metalloproteases [28]. When ugtP + cells were challenged by hen egg white lysozyme (HEWL) at low concentration (100 ng/mL), …”
Section: 10-phenanthroline Inhibited Activation Of σ V Caused By Admentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that PrsW, the site-1 protease, is the sensor of the environmental stressor (Ellermeier & Losick, 2006), but further research into the mechanism suggests the involvement of a negative regulator of proteolysis in sensing the stress signal (Heinrich et al, 2009). More recently, the regulation of s V by its anti-s factor RsiV has been investigated (Hastie et al, 2013(Hastie et al, , 2014). Like the s W stress response, the s V stress response chemically remodels cell envelope structure providing resistance to its inducer, lysozyme (Guariglia-Oropeza & Helmann, 2011;Ho et al, 2011).…”
Section: Introductionmentioning
confidence: 99%